A review of diffuse interface-capturing methods for compressible multiphase flows - Adebayo, Ebenezer Mayowa; Tsoutsanis, Panagiotis; Jenkins, Karl W. (MDPI, 2025)
This paper discusses in detail the classification, historical development, and application of diffuse interface-capturing models (DIMs) for compressible multiphase flows. The work begins with an overview of the development of DIMs, highlighting important contributions and key moments from classical studies to contemporary advances. The theoretical foundations and computational methods of the diffuse interface method are outlined for the full models and the reduced models or sub-models. Some of the difficulties encountered when using DIMs for multiphase flow modelling are also discussed.
This article belongs to the Special Issue Compressible Flows
Keywords: 4012 Fluid Mechanics and Thermal Engineering; 40 Engineering; 4012 Fluid mechanics and thermal engineering; diffuse interface models; compressible multiphase flow; interface capturing; Baer–Nunziato